2020
DOI: 10.1080/1828051x.2020.1784804
|View full text |Cite
|
Sign up to set email alerts
|

Combining total and differential somatic cell count to better assess the association of udder health status with milk yield, composition and coagulation properties in cattle

Abstract: Cassandro (2020) Combining total and differential somatic cell count to better assess the association of udder health status with milk yield, composition and coagulation properties in cattle,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Moreover, the recent implementation of new advanced milk-testing technology has allowed measurement of both traditional somatic cell count (SCC) and new differential somatic cell count (DSCC), which is the ratio of neutrophils plus lymphocytes to total SCC [ 14 ]. This novel udder health trait provides more detailed insights on the inflammatory status of the mammary gland and the combined use of SCC and DSCC has been proposed as a novel approach to screen for udder health status [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the recent implementation of new advanced milk-testing technology has allowed measurement of both traditional somatic cell count (SCC) and new differential somatic cell count (DSCC), which is the ratio of neutrophils plus lymphocytes to total SCC [ 14 ]. This novel udder health trait provides more detailed insights on the inflammatory status of the mammary gland and the combined use of SCC and DSCC has been proposed as a novel approach to screen for udder health status [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For all tested periods, DSCC was always below 70%, with the only exception of the MLG period (70.22%; Table 5 ), which was close to the threshold proposed by Zecconi et al [ 53 ] to identify subclinical mastitis. The results of the present study suggest only a slight deterioration of mammary health status at the end of the summer season (i.e., MLG), mostly in terms of udder susceptibility rather than the onset of overt mastitis [ 29 ]. As for DSCC, comparison with the literature is difficult since, to the authors’ knowledge, this is the first study that has investigated DSCC before and during grazing.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the recent implementation of new milk-testing technologies has allowed the routine recording of differential somatic cell count (DSCC), which is the ratio of neutrophils plus lymphocytes to the total SCC [ 28 ]. The novel DSCC trait, in combination with traditional SCC, provides a more precise indication of dairy cows’ udder health status and helps farmers identify healthy cows from those susceptible to the disease or with acute or chronic mastitis [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that cows in groups B, C, and D produced 0.9–2.4%, 6–9.8%, and 17.5–38.5% less milk than cows in group A, respectively. The same approach was used by Bobbo et al ( 35 ) to study the association between milk yield and composition and SCC combined with F-DSCC. The authors found that cows in group B had slightly higher milk production than those in group A, while cows in groups C and D had lower milk production than those in groups A and B.…”
Section: Dscc and Milk Productionmentioning
confidence: 99%
“…The authors found that cows in group B had slightly higher milk production than those in group A, while cows in groups C and D had lower milk production than those in groups A and B. The picture was opposite for fat and protein production, perhaps due to a concentration effect as a result of the reduced milk production ( 35 ). In another recent study, Zecconi et al ( 32 ) found no significant association between milk production and F-DSCC for cows with SCC <50,000 cells/ml.…”
Section: Dscc and Milk Productionmentioning
confidence: 99%